2009
DOI: 10.1074/jbc.m109.055897
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the Par Polarity Complex Protein Par3 at Serine 962 Is Mediated by Aurora A and Regulates Its Function in Neuronal Polarity

Abstract: The Aurora kinases are a family of serine/threonine protein kinases that perform important functions during the cell cycle. Recently, it was shown that Drosophila Aurora A also regulates the asymmetric localization of Numb to the basal and the partitioning-defective (Par) complex to the apical cortex of neuroblasts by phosphorylating Par6. Here, we show that Aurora A is required for neuronal polarity. Suppression of Aurora A by RNA interference results in the loss of neuronal polarity. Aurora A interacts direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 40 publications
3
27
0
1
Order By: Relevance
“…Because two aPKC‐binding variants showed disruption of tight junction formation, we transfected siRNA into human NPCs to develop an in vitro cellular model with PARD3 knockdown, and then examine the phenotypic characteristics of the NPCs. The PARD3/PARD6 complex was reported to display apical polarity in human neural progenitors, which is different from what was seen in MDCK cells [Wolf, et al., ; Khazaei and Puschel, ]. We confirmed that PARD3 was apically localized on NPCs undergoing mirror‐symmetry divisions (white arrow in Supp.…”
Section: Resultssupporting
confidence: 66%
“…Because two aPKC‐binding variants showed disruption of tight junction formation, we transfected siRNA into human NPCs to develop an in vitro cellular model with PARD3 knockdown, and then examine the phenotypic characteristics of the NPCs. The PARD3/PARD6 complex was reported to display apical polarity in human neural progenitors, which is different from what was seen in MDCK cells [Wolf, et al., ; Khazaei and Puschel, ]. We confirmed that PARD3 was apically localized on NPCs undergoing mirror‐symmetry divisions (white arrow in Supp.…”
Section: Resultssupporting
confidence: 66%
“…A hypomorphic alíele of Aurora A impairs asymmetric localization of the basal asymmetric marker Numb and increases the number of symmetric cell divisions. These defects are thought to be caused by altered dynein-dependent spindle orientation and delocalization of specific cortical markers such as aPKC or Numb recruited through the Aurora A-dependent phosphorylation of Dlg(Pins), Par-3, and Par-6 (158, 169,187,353). Aurora B may also play a role in asymmetric cell division as its CPC partner INCENP is required for the asymmetric segregation of Prospero during asymmetric neuroblast division in Drosophila (58).…”
Section: Figurementioning
confidence: 98%
“…However, in C. elegans , there is no evidence for AIR-1 to be involved in PLK-1 activation [84]. Alternatively, AIR-1 could control polarity more directly by phosphorylating polarity components, as is the case in D. melanogaster , where Aurora A phosphorylates Par6 and aPKC [88,89], or in mammalian neurons, where Aurora A phosphorylates Par3 [90]. …”
Section: Coupling Cell Polarity and Cell Cycle Progression In Caenorhmentioning
confidence: 99%